Effect of density of steam flaked milo on animal performance, mill production rate, and subacute acidosis - Robert T. Brandt Jr.; A.S. Freeman; T.P. Eck; Christopher D. Reinhardt; Keith C. Behnke (Kansas Agricultural Experiment Station Research Reports, 1993)
In Trial 1, 336 yearling steers (755 lb) were fed diets containing milo flaked to 22 (L), 25 (M), or 28 (H) lb/bu. The steers fed L consumed 3.2% less dry matter than cattle fed H (P<.05) and had 6.9% lower gains (P<.05). Feed efficiency tended (P=.15) to favor cattle fed H. The H milo was flaked 27% faster than M and 67% faster than L (P<.0001), resulting in lower production cost for the heavy flakes. In Trial 2, six ruminally cannulated steers were fed the same diets used in Trial 1 in a replicated 3x3 Latin square. After adaptation to the respective diets, the cattle were fasted and then overfed to simulate a drastic intake fluctuation. The L diet was fermented more rapidly than the H diet, resulting in greater ruminal pH depression (P<.10) following overconsumption. Under the conditions of this experiment, flaking milo more intensively than 28 lb/bu (58.7% starch gelatinization) resulted in decreased consumption, lower mill efficiency, and increased propensity for acidosis in finishing steers.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Steam flaking; Milo; Density; Acidosis; Mill Efficiency